Autophagy inhibits cancer stemness in triple‐negative breast cancer via miR‐181a‐mediated regulation of ATG5 and/or ATG2B. Issue 9 (26th January 2022) - Park, Jee Won; Kim, Yesol; Lee, Soo‐been; Oh, Chae Won; Lee, Eun Ji; Ko, Je Yeong; Park, Jong Hoon
Abstract : Autophagy has a dual role in the maintenance of cancer stem cells (CSCs), but the precise relationship between autophagy and cancer stemness requires further investigation. In this study, it was found that luminal and triple‐negative breast cancers require distinct therapeutic approaches because of their different amounts of autophagy flux. We identified that autophagy flux was inhibited in triple‐negative breast cancer (TNBC) CSCs. Moreover, miRNA‐181a (miR‐181a) expression is upregulated in both TNBC CSCs and patient tissues. Autophagy‐related 5 (ATG5) and autophagy‐related 2B (ATG2B) participate in the early formation of autophagosomes and were revealed as targets of miR‐181a. Inhibition of miR‐181a expression led to attenuation of TNBC stemness and an increase in autophagy flux. Furthermore, treatment with curcumin led to attenuation of cancer stemness in TNBC CSCs; the expression of ATG5 and ATG2B was enhanced and there was an increase of autophagy flux. These results indicated that ATG5 and ATG2B are involved in the suppression of cancer stemness in TNBC. In summary, autophagy inhibits cancer stemness through the miR‐181a‐regulated mechanism in TNBC. Promoting tumor‐suppressive autophagy using curcumin may be a potential method for the treatment of TNBC. Abstract : Triple‐negative breast cancer (TNBC) is the most aggressive subtype of breast cancer. However, potential therapeutic targets in TNBC have not been fully elucidated. In this study, we identified the tumor‐suppressive role of miR‐181a and investigated the role of miR‐181a in regulating autophagy and TNBC stemness. Inhibition of miR‐181a elicited tumor‐suppressive effects by inducing autophagy and may thus be considered as a potential therapeutic strategy in patients with TNBC.